Studi Penafsiran Ayat-Ayat Al-’Afw Dan Ash-Shafh dalam Tafsir Al-Azhar - Faridah, Faridah; Rokhani, Siti; Mukminah, Raisatul; Putra, Rizky Pratama (Al Ashriyyah, 2024)
The abstract should be clear, concise, and descriptive. This abstract should provide a brief introduction to the problem, objective of paper, followed by a statement regarding the methodology and a brief summary of results. The abstract should end with a comment on the significance of the results or a brief conclusion. Abstracts are written in 11 pt Times New Roman, preferably not more than 300 words. A person's morals will be tested when he is caught in a dispute either between individuals or groups when they interact with each other, so as long as humans are still interacting with each other, disputes will always exist. This condition human beings are required to understand each other's behavior by forgiving them. The Qur'an mentions several terms to refer to forgiving and attempting to establish a good relationship between man and Allah, namely it is taba, al-’afw, ghafara, kaffara and ash-shafh. However, this study only discusses verses that mention al-’afw and ash-shafh in one verse. Because of the 8 times the word ash-shafh, 4 of them are side by side with the word al-’afw. The purpose of this study is to find out Hamka's interpretation of the verses of al-’afw and ash-shafh in Tafsir Al-Azhar. It is also to know the contextualization of the interpretation of the verses of al-’afw and ash-shafh in Tafsir Al-Azhar with the social life of the people. This research is included in the type of library research, using a descriptive-analytical method, namely explaining clearly, in detail, and relating matters related to information related to the Qur'an. The data collection technique uses documentation techniques, namely collecting data related to the object of research from the book of interpretation and books relevant to the discussion. The results of this study found that Hamka interpreted the word al-’afw with forgiveness. Meanwhile, the word ash-shafh is interpreted with a chest-to-chest and letting in by not taking the heart of the guilty. As for the contextual interpretation of the verses of al-’afw and ash-shafh in this study is: the command of forgiveness remains commanded on infidels as long as their mistakes are not related to Shi'ar Islam. But if their mistakes are detrimental to the glory of Islam then they must be fought until they pay the jizyah. The order of forgiveness is given to fellow Muslim brothers and family without having to wait for an apology. Accompanied by an airy attitude of the chest by continuing to do good to them just as before there was a conflict and guiding them to kindness accompanied by affection and do'a so that they return to the truth